2017
DOI: 10.3171/2017.5.focus17146
|View full text |Cite
|
Sign up to set email alerts
|

Fully endoscopic lumbar interbody fusion using a percutaneous unilateral biportal endoscopic technique: technical note and preliminary clinical results

Abstract: OBJECTIVEMinimally invasive spine surgery can minimize damage to normal anatomical structures. Recently, fully endoscopic spine surgeries have been attempted for lumbar fusion surgery. In this study, the authors performed a percutaneous unilateral biportal endoscopic (UBE) technique as a minimally invasive surgery for lumbar fusion. The purpose of this study is to present the UBE technique of fully endoscopic lumbar interbody fusion (LIF) and to analyze the clinical r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
206
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 219 publications
(219 citation statements)
references
References 14 publications
4
206
0
1
Order By: Relevance
“…[10] Bleeding from endplate is the sign of complete endplate preparation. [5,9,18] In order to see bony bleeding with other procedure such as conventional MIS-TLIF, open TLIF, OLIF, and ALIF are usually impossible due to limited working space. We usually just feel using the reamer whether it is already the endplate yet.…”
Section: Discussionmentioning
confidence: 99%
“…[10] Bleeding from endplate is the sign of complete endplate preparation. [5,9,18] In order to see bony bleeding with other procedure such as conventional MIS-TLIF, open TLIF, OLIF, and ALIF are usually impossible due to limited working space. We usually just feel using the reamer whether it is already the endplate yet.…”
Section: Discussionmentioning
confidence: 99%
“…The working cannula was then replaced with a custommade working sheath (16-20 mm outer diameter) so a cage could be implanted. Heo DH et al [14] used two channels (an endoscopic portal and a working portal) to perform an endoscopic lumbar fusion surgery. In this case, an ipsilateral facetectomy and partial hemilaminectomy were performed to create su cient space to operate.…”
Section: Discussionmentioning
confidence: 99%
“…The pedicle screw insertion in ELIF was also a minimally invasive by percutaneous techniques, it preserved the musculotendinous attachments and the integrity of lumbar fascia. [14] Mandy studies comparing traditional TLIF to PLIF showed equal or better results with the transforaminal approach. Sufficient decompression with no retraction on the nerve ganglion, less postoperative pain and earlier functional recovery were the major advantages of the transforaminal approach.…”
Section: Introductionmentioning
confidence: 97%
“…[5,15] With lumbar spine techniques development, the procedures of nerve decompression and interbody fusion was completed with maintain the facet intact, pedicle screw was placement by minimally invasive percutaneous techniques with preservation of musculotendinous attachments, ELIF true minimally invasive surgery has less blood loss, earlier postoperative recovery, and decreased rates of infection in comparison to open surgery. [16][17][18]14,19] The purpose of this study was to evaluate the efficacy of endoscopic transforaminal lumbar interbody fusion in the treatment of degenerative lumbar spondylolisthesis by compare to the standard transforaminal lumbar interbody fusion in our clinical.…”
Section: Introductionmentioning
confidence: 99%